Yoga inside and outside : carrying inner bliss into your life - Saraswati, Swami Nirmalananda ([Ashland, Ohio] : Svroopa Teaching Collections, Inc., 2011)
The newest collection of Swami Nirmalananda's monthly teachings, Yoga: Inside & Outside, shows you how to carry your yoga into your life. The basis is bliss, the inner bliss you experience when you do yoga. Once you have experienced your own innermost Self, life looks and feels different to you. Each article weaves the inside and outside together, with profound teachings and practical pointers, Sanskrit sutras and down-to-earth methodologies for making your life a yogic life. Swamiji's first collection, Yoga in Every Moment, offers 10 years of articles that cover the breadth of yoga's philosophy. This collection covers eight years with more in-depth teachings that are easily accessible to the brand-new reader. You can read the book from front to back, or wander around in any order that suits you -- Swamiji's unassuming manner and unfailing good humor will open you to a new way of living your yoga.
Description based on print version record.
Keywords: Yoga; HEALTH & FITNESS / Yoga; RELIGION / Hinduism / General; Electronic books